DEVELOPMENT OF A DATA ACQUISITION SYSTEM FOR PHOTOVOLTAIC SYSTEMS - Reges, Jonas Platini; Oliveira, Francisco Ismael de; Sousa, José Renato de Brito; Carvalho, Paulo Cesar Marques; Alexandria, Auzuir Ripardo de (Revista Brasileira de Energia Solar, 2021)
The generation of energy through alternative renewable sources for the Brazilian energy matrix is very important for the safety of the electric energy network, due to the diversification of the fundamental elements for power generation. Therefore, photovoltaic systems are a good solution for this application for they have a relatively growing energy efficiency. The monitoring in the generation of electric energy is essential as a way to analyze statistically the yields of electric power generation and to validate the technical feasibility of the system. The objective of this work is the development of a data acquisition system which aims at an analysis on the performance of photovoltaic systems. This work is motivated by the implementation of a monitoring system with electrical insolation through optocouplers in the measurement, having the ability to readjust the modules and allowing the insertion of new sensors or shields. The monitoring system was developed in the Arduino platform, a platform of electronic prototyping of free hardware. The photovoltaic solar system was installed in the area of the Federal Institute of Education, Science and Technology of Ceará – Campus Jaguaribe. In total, 3 tests are performed with the monitoring system whose results are presented and evaluated. The results are analyzed with the purpose of evaluating the performance of the monitoring system as to measurement error and measurement accuracy. Then, a general analysis about the operation of the monitoring system is performed. The main contribution of this work is the development of the data acquisition system.